Thailand : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2009)
This paper discusses key findings of the Financial System Stability Assessment (FSSA) on Thailand. The assessment reveals that the soundness of Thailand's financial system has been strengthened since the financial crisis of the late 1990s. Substantial progress has been made in upgrading the regulatory and supervisory system and improving macroeconomic management. Banking fundamentals have strengthened, with most Thai banks reporting high levels of capital and solid profitability. Private corporations, which are the banks' primary borrowers, have also strengthened their balance sheets and reduced leverage.